2021
DOI: 10.21203/rs.3.rs-1082320/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Music-Based Intervention Connects Auditory and Reward Systems

Abstract: Listening to pleasurable music is known to engage the brain’s reward system. This has motivated many cognitive-behavioral interventions for healthy aging, but little is known about the effects of music-based intervention (MBI) on plasticity of the cognitive and reward systems. Here we show preliminary evidence that brain network connectivity can change after receptive MBI in cognitively unimpaired older adults. Using a combination of whole-brain regression, seed-based connectivity analysis, and representationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…As part of a larger project on the development of a novel music-based intervention (MBI) for aging, in the current study, participants listened to self-selected music during a period of audiovisual stimulation. Participants were explicitly instructed to select their own music for the audiovisual stimulation, as self-selected music represents a more ecologically valid music listening experience that is linked to efficacy of MBIs [ 25 ] and increases neural activity across auditory and reward systems [ 8 , 11 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As part of a larger project on the development of a novel music-based intervention (MBI) for aging, in the current study, participants listened to self-selected music during a period of audiovisual stimulation. Participants were explicitly instructed to select their own music for the audiovisual stimulation, as self-selected music represents a more ecologically valid music listening experience that is linked to efficacy of MBIs [ 25 ] and increases neural activity across auditory and reward systems [ 8 , 11 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such variability in the efficacy of music-based interventions may arise, in part, from the diversity of protocols that underlie MBIs (e.g., self-selected vs. clinician-selected music), the heterogeneity of clinical populations that are targeted by MBIs, and individual differences in the sensitivity to musical features that constitute the intervention (e.g., rhythm, melody, motor-movement, and social interactions during musical experiences) [ 4 , 7 , 8 ]. While research has identified key neural networks that contribute to music processing [ 9 , 10 ], little is known about the underlying neurobiological mechanisms that are specifically engaged by MBIs [ 11 , 12 ], and how aging affects neural responses to musical structure (e.g., rhythm, melody, and harmony) [ 13 ]. However, understanding how MBIs engage the nervous system and the impact of aging on the neural processing of music has important implications for designing and implementing MBIs; understanding the effects of naturalistic music-listening and -making on brain function, cognitive health, and well-being; and explaining individual outcomes following the intervention [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of a larger project on the development of a novel music-based intervention (MBI) for aging, in the current study, participants listened to self-selected music during a period of audiovisual stimulation. Participants were explicitly instructed to select their own music for the audiovisual stimulation, as self-selected music represents a more ecologically valid music listening experience that is linked to efficacy of MBIs (Leggieri et al, 2019) and increases neural activity across auditory and reward systems (Blood & Zatorre, 2001; Loui, 2020; Quinci et al, 2021; Salimpoor et al, 2013).…”
Section: Discussionmentioning
confidence: 99%